The Effect of Stirring Speed and pH on the Synthesis of Calcium Nitrate Fertilizer from Eggshell Waste Using Precipitation Method - Latifa Chusnul Primadhani; Thoriqul Hilmi Afan Mathovani; Sintha Soraya Santi; Ketut Sumada; Dyah Suci Perwitasari (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Eggshell waste is a calcium-rich biomaterial with high potential as a raw material for fertilizer production. This study investigates the effect of stirring speed and pH on the synthesis of calcium nitrate from chicken eggshells using a dissolution–precipitation method. The process involved dissolution in nitric acid (HNO?) followed by precipitation using ammonium hydroxide (NH?OH) at varying stirring speeds (200–400 rpm) and pH levels (5–9). The products were analysed using X-ray fluorescence (XRF), SEM-EDX, and yield calculations. XRF analysis showed that the eggshell contained 98.72% calcium. The results indicated that increasing stirring speed improved yield, while pH significantly affected product composition. The optimum condition was obtained at pH 7 and 400 rpm, yielding calcium and nitrogen contents of 29.47% and 16.93%, respectively, which meet the Indonesian National Standard (SNI 02-2806-1992). These findings demonstrate that eggshell waste can be effectively used as an alternative raw material for the production of calcium nitrate fertiliser. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land